THE PAYMENT OF WAGES - Alberto Benítez Sánchez (Denarius, 2010)
This article studies the effects on income distribution caused by changes in the fraction of wages paid at the start of a production program, when the remaining wage is paid at the end. Among other results, it is found that this fraction permits the definition of certain restrictions affecting the form of the wage-profit curve as well as other constraints influencing Wicksell effects on prices.